Impacts of higher-order dispersion coefficients and dispersion fluctuations on one-pump fiber optical parametric amplifier - Othman, Nurulanati (2019)
Four-wave mixing (FWM) is a nonlinear effect in optical fiber which is useful for fiber optical parametric amplifiers (FOPA). The performance of FOPA i.e. parametric gain, amplification bandwidth, and saturation power are reliant on the efficiency of the FWM process. The random dispersion fluctuations (